Retention of fatty acyl desaturase 1 (fads1) in Elopomorpha and Cyclostomata provides novel insights into the evolution of long-chain polyunsaturated fatty acid biosynthesis in vertebrates ... - Lopes-Marques, Mónica; Kabeya, Naoki; Qian, Yu; Ruivo, Raquel; Santos, Miguel; Venkatesh, Byrappa; Tocher, Douglas; Castro, L.; Monroig, Óscar (figshare, 2018)
Abstract Background Provision of long-chain polyunsaturated fatty acids (LC-PUFA) in vertebrates occurs through the diet or via endogenous production from C18 precursors through consecutive elongations and desaturations. It has been postulated that the abundance of LC-PUFA in the marine environment has remarkably modulated the gene complement and function of Fads in marine teleosts. In vertebrates two fatty acyl desaturases, namely Fads1 and Fads2, encode ∆5 and ∆6 desaturases, respectively. To fully clarify the evolutionary history of LC-PUFA biosynthesis in vertebrates, we investigated the gene repertoire and function of Fads from species placed at key evolutionary nodes. Results We demonstrate that functional Fads1Δ5 and Fads2∆6 arose from a tandem gene duplication in the ancestor of vertebrates, since they are present in the Arctic lamprey. Additionally, we show that a similar condition was retained in ray-finned fish such as the Senegal bichir and spotted gar, with the identification of fads1 genes in ...